Re(claiming) Subjectivity and Transforming the Politics of Silence through the Search for Wholeness in Push by Sapphire - Castro Borrego, Silvia Pilar (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2014)
Post-positivist realism contends that there is a need to theorize not only identity but also agency. Identity is hence understood from the dialogic perspective of engaging the world from the vantage point of agency, facilitating wholeness, or the dialogic interaction between self and other, past and present. The search for wholeness with the aid of re-memory, double consciousness and agency becomes the trigger for an active expression of Black women’s subjectivity throughout the African diaspora. Women’s subjectivity consists of giving emphasis to the importance of women being the owners of their destinies when they engage in the building of their identities, which are shaped by the interaction of time, community and experience, claiming that identity is performative, indeterminant and multiple. Sapphire’s novel Push will be analyzed as a text that counteracts the politics of silence, transforming fear and difference into speech and telling, adding to the liberatory discourses of contemporary Black women writers.